(untitled) (BIRDEM Medical Journal, 2019)
Background: Cervical spondylotic myelopathy (CSM) is a progressive degenerative disease and the most common cause of cervical spinal cord dysfunction (SCD) in older patients. Anterior cervical discectomy andfusion (ACDF) is a common procedure for patients with severe neurological deterioration. The goals of this study were to evaluate the clinical and functional outcome, radiological fusion and operative complications in case of CSM who underwent ACDF by autogeneous-tricortical bone graft and stabilized with plate and screws. Methods: This prospective interventional study was carried out at National Institute of Traumatology and Orthopaedic Rehabilitation ( NITOR) and different private hospitals in Dhaka from January 2012 to December 2014. Within this period total 12 CSM patients were included as study sample. All were surgically treated by ACDF and stabilized by plate and screws. All patients were clinically and radiologically evaluated before and after surgery. Results: Single level ACDF by autograft and stabilization by plate and screws was done in 10 (83.33%) patients and 2 (16.67%) patients had two level fusion. The mean follow up period was 12 months. The satisfactory result was found in 10 (83.33%) patients. Post-operative complications were donor site morbidity in2 (16.67%) patients and transient dysphagia in 1 (8.33%) patient. The fusion rate was 100% in this series. Conclusion: ACDF with anterior plating for CSM is a safe and effective procedure. It results in highest fusion, least complication and relatively lower cost. Birdem Med J 2019; 9(2): 133-137